GRB2-mediated recruitment of THEMIS to LAT is essential for thymocyte development. - Paster, W; Brockmeyer, C; Fu, G; Simister, P; de Wet, B; Martinez-Riaño, A; Hoerter, J; Feller, S; Wülfing, C; Gascoigne, N; Acuto, O (2013)
Thymocyte-expressed molecule involved in selection (THEMIS) is a recently identified regulator of thymocyte positive selection. THEMIS's mechanism of action is unknown, and whether it has a role in TCR-proximal signaling is controversial. In this article, we show that THEMIS and the adapter molecule growth factor receptor-bound protein 2 (GRB2) associate constitutively through binding of a conserved PxRPxK motif within the proline-rich region 1 of THEMIS to the C-terminal SH3-domain of GRB2. This association is indispensable for THEMIS recruitment to the immunological synapse via the transmembrane adapter linker for activation of T cells (LAT) and for THEMIS phosphorylation by Lck and ZAP-70. Two major sites of tyrosine phosphorylation were mapped to a YY-motif close to proline-rich region 1. The YY-motif was crucial for GRB2 binding, suggesting that this region of THEMIS might control local phosphorylation-dependent conformational changes important for THEMIS function. Finally, THEMIS binding to GRB2 was required for thymocyte development. Our data firmly assign THEMIS to the TCR-proximal signaling cascade as a participant in the LAT signalosome and suggest that the THEMIS-GRB2 complex might be involved in shaping the nature of Ras signaling, thereby governing thymic selection.